The choice for invasive prenatal tests after subfertility. (2nd April 2020) - Hendrix, Manouk; Arits, Jolijn; Bannink, Roy; van Montfoort, Aafke; Willekes, Christine; den Hartog, Janneke; Al-Nasiry, Salwan
Abstract: The aim of this study was to test whether women who conceived after a period of subfertility are less likely to undergo invasive prenatal testing (IPT) and determine factors of influence in that decision. We conducted a retrospective study at the Maastricht University Medical Centre (MUMC+) to compare the rates of IPT following abnormal results of combined first trimester screening (cFTS) or second trimester screening (STS), or because of advanced maternal age among women tested for the effect of type and duration of subfertility and history of fertility investigations and/or treatment. We included 977 women who underwent IPT between January 2010 and December 2013. The women who conceived after fertility investigations and/or treatment had lower rates of IPT following abnormal STS (12.6% vs. 20.0%, OR = 0.58, 95% CI; 0.34–0.97). The difference was not statistically significant after correction for maternal age and severity of the foetal anomaly. Maternal age was, in contrast to fertility treatment or duration of subfertility, related to the choice of IPT among formerly subfertile women. Therefore, the lower uptake of IPT in women conceiving after a period of subfertility is dependent on the indication for IPT and maternal age and less on the type and duration of subfertility.